Characterization of Hysterectomy in Women with VWD Using Data from a US Medical Claims Database - Sidonio, Robert F.; Hale, Sarah A; Halari, Imrran; Zia, Ayesha (Blood, 2020)
Background: Von Willebrand disease (VWD) is the most common inherited bleeding disorder in women. Heavy menstrual bleeding (HMB) is a frequent symptom with a significant impact on the quality of life, but its management is complicated by delayed recognition and diagnosis of VWD. Hysterectomy or uterine ablation (UA) may be performed for refractory HMB, but has profound consequences for women, particularly those of child-bearing age. Objective: To assess rates of hysterectomy/ UA in women before and after diagnosis of VWD, and evaluate hysterectomy/UA (including age at procedure) in women with VWD compared to women without a bleeding disorder, using medical claims data. Methods: We analyzed data from subjects enrolled in the IMS PharMetrics Plus Database of medical insurance claims between July 2013 and June 2015. Data were extracted for female subjects with diagnosed VWD (defined as ≥2 medical claims for VWD [ICD-9 code 286.4]), and for a sample of 10,000 “no bleeding disorder [NBD]” subjects (no history of a bleeding disorder via medical claim or of product use for any bleeding disorder). Occurrence of hysterectomy/UA was compared in the following populations, with time periods aligned to cover the most recent year: VWD patients with continuous enrollment (CE) in the most recent year (N=5257) and NBD patients with CE in the most recent 2 years (N=5673). A VWD subpopulation with enrollment in the 2 years before and after diagnosis (N=1181) was used for analysis of hysterectomy/UA rates pre- and post- diagnosis. Age at hysterectomy/UA was analyzed for patients with CE for 1 year before and after their procedure. Bleed claims in the 1 year before and the 6 to 18 months after hysterectomy/UA were analyzed for patients with CE over this timeframe. Groups were compared using the t-test (mean age at hysterectomy) and Chi-squared test (other outcomes). Results: More women without a bleeding disorder (NBD group) than with VWD had undergone hysterectomy or UA within the most recent year (105/5673 [1.9%] versus 60/5257 [1.1%]; P=0.0024). Among women with VWD, the rate of hysterectomy/UA was higher after VWD diagnosis than before (69/1181 [5.8%] versus 41/1181 [3.5%] women; P=0.0063). When evaluating women with 1 year of enrollment before and after the procedure, 246 (VWD) and 578 (NBD) women with hysterectomy/UA were identified. Among these women with VWD and NBD, there was no significant difference in mean age at hysterectomy/UA (41 versus 43 years; P=0.9997). However, a significantly greater proportion of women with hysterectomy/UA in the VWD compared with the NBD group were aged ≤40 years (110/246 [44.7%] versus 208/578 [36.0%], P=0.0185), and ≤35 years (58/246 [23.6%] versus 86/578 [14.9%]; P=0.0026). Claims for all bleeds (including HMB) were significantly reduced following hysterectomy/UA, but some patients continued to bleed. Among women with VWD, 200/226 (88.5%) and 48/226 (21.2%) had bleed claims before and after the procedure, respectively (P<0.0001), as did 404/531 (76.1%) and 41/531 (7.7%) of women with NBD (P<0.0001). Of the 48 women with VWD who had bleed claims following their procedure, 37 (77.1%) had claims for HMB. Bleed claims were significantly more common among women with VWD than with NBD, both before and after hysterectomy/UA (both P<0.0001). Conclusions: Surprisingly, rates of hysterectomy/UA increased among women with VWD following their diagnosis. Among women who underwent hysterectomy/UA, those with VWD were on average younger than those with NBD. Despite the perception of hysterectomy/UA as an effective treatment for HMB, our analysis indicates around one in five women with VWD may continue to have HMB bleed claims after this procedure. These data underscore a significant need for improved and optimized treatment in women with VWD, to control HMB and other bleeding episodes, and to prevent or delay hysterectomy/UA. Sidonio:Bayer, Bioverativ/Sanofi, Novo Nordisk, Takeda, Uniqure, Biomarin, Octapharma, Catalyst, Grifols, Sigilon, Tremeau, Genentech/Roche: Consultancy; Octapharma, Grifols, Takeda and Genentech: Research Funding. Hale:Takeda Pharmaceutical Company Limited: Current Employment. Halari:Charles River Associates: Current Employment.